An improved full search block matching algorithm for imaging applications - AlDabbagh, S.S.M.; Mabrouk, A.H.; Alshaikhli, Imad Fakhri Taha (2012)
Full search block matching algorithm (FSBMA) for motion estimation requires a high level of computations, rendering the technique unsuitable for real-time imaging applications. To alleviate this problem, extensive research for developing faster motion estimation techniques has been conducted. As expected, reducing computational complexity comes at the expense of the image quality. This paper presents an improved full search block matching algorithm (IFSBMA) that reduces the computational load without significant degradation of the image quality. In comparison with other full search algorithms, the proposed technique reduces computational intensity with almost 90% for video bowing and 95% for video test. Experimental results also show that the computational complexity of the proposed technique is relatively higher than that of the four-step (FSS) and the three-step (TSS) algorithms. However, the sum of absolute difference (SAD) of the proposed technique is better than the SAD of the FSS and the TSS.